High-intensity focused ultrasound therapy in combination with gemcitabine for unresectable pancreatic carcinoma - Lv W; Yan T; Wang G; Zhao W; Zhang T; Zhou D (Dove Medical Press, 2016)
Wei Lv, Tao Yan, Guojin Wang, Wei Zhao, Tao Zhang, Dinghua Zhou Hepatobiliary Surgery Department, Second Artillery General Hospital, Xicheng District, Beijing, People’s Republic of China Objective: To investigate the therapeutic effect and safety of high-intensity focused ultrasound (HIFU) therapy combined with gemcitabine in treating unresectable pancreatic carcinoma. Methods: The 45 patients suffering from pancreatic carcinoma were randomized into two groups. The patients in the experimental group (n=23) received HIFU in combination with gemcitabine and those in the control group (n=22) received gemcitabine alone. The effect and clinical benefit rates in the two groups were compared. The median survival time and 6-month and 12-month survival rates were calculated by Kaplan–Meier method and log-rank test. Results: The median survival time and 6-month survival rate were significantly higher in the experimental group than in the control group (8.91 months vs 5.53 months, 73.9% vs 40.9%, respectively P<0.05), but 12-month survival rate was not statistically different between the two groups (13.0% vs 4.5%, P>0.05). The clinical benefit rates in the experimental group and the control group were 69.6% and 36.3%, respectively (P<0.05). The pain remission rate in the experimental group was significantly higher than that in the control group (65.2% vs 31.8%, P<0.05). Conclusion: HIFU in combination with gemcitabine is better than gemcitabine alone. This combinatorial therapy may become a better and effective treatment for unresectable pancreatic carcinoma. Keywords: pancreatic carcinoma treatment, high-intensity focused ultrasound therapy, gemcitabine